Features of the assessment of the mongolian religious policy by russian researchers (Journal of history, 2019)
Аuthors of the article conditionally divided the historiography into two groups: surveystudies; special works devoted to the study of sources. Based on the analysis, the researchers determinedthe features of the assessment of the Mongolian religious policy. They defined the researcher’sapproach to this problem. In the article it was characterized the conceptual approach and was carriedout a comparative analysis of the religious policy of the Mongols in the modern period. It is shown thatthe conclusions of the authors became the foundation for subsequent works in this direction. It was madean attempt to show the continuity of scientific views and those aspects of this problem that have yet tobe revealed. Despite the small number of works and their specificity, we can say that pre-revolutionaryhistorians managed to solve a number of complex problems: it was formulated a more or less objectiveview of the religious policy of the Mongol khans; at the result of the introduction of a large number ofdifferent sources into scientific circulation, it was formed a critical view of the problem; there was anunderstanding that the relationship of the Mongol khans with the conquered peoples was not unambiguous;methods of studying history (positivism) appeared; a calmer view of the activities of the Mongolrulers, including in the field of religious policy, has taken shape.